C-reactive protein, established risk factors and social inequalities in cardiovascular disease - the significance of absolute versus relative measures of disease - Hedblad Bo; Berglund Göran; Engström Gunnar; Rosvall Maria (BMC, 2008)
Abstract Background The widespread use of relative scales in socioepidemiological studies has recently been criticized. The criticism is based mainly on the fact that the importance of different risk factors in explaining social inequalities in cardiovascular disease (CVD) varies, depending on which scale is used to measure social inequalities. The present study examines the importance of established risk factors, as opposed to low-grade inflammation, in explaining socioeconomic differences in the incidence of CVD, using both relative and absolute scales. Methods We obtained information on socioeconomic position (SEP), established risk factors (smoking, hypertension, and hyperlipidemia), and low-grade inflammation as measured by high-sensitive (hs) C-reactive protein (CRP) levels, in 4,268 Swedish men and women who participated in the Malmö Diet and Cancer Study (MDCS). Data on first cardiovascular events, i.e., stroke or coronary event (CE), was collected from regional and national registers. Social inequalities were measured in relative terms, i.e., as ratios between incidence rates in groups with lower and higher SEP, and also in absolute terms, i.e., as the absolute difference in incidence rates in groups with lower and higher SEP. Results Those with low SEP had a higher risk of future CVD. Adjustment for risk factors resulted in a rather small reduction in the relative socioeconomic gradient, namely 8% for CRP (≥ 3 mg/L) and 21% for established risk factors taken together. However, there was a reduction of 18% in the absolute socioeconomic gradient when looking at subjects with CRP-levels < 3 mg/L, and of 69% when looking at a low-risk population with no smoking, hypertension, or hyperlipidemia. Conclusion C-reactive protein and established risk factors all contribute to socioeconomic differences in CVD. However, conclusions on the importance of "modern" risk factors (here, CRP), as opposed to established risk factors, in the association between SEP and CVD depend on the scale on which social inequalities are measured. The one-sided use of the relative scale, without including a background of absolute levels of disease, and of what causes disease, can consequently prevent efforts to reduce established risk factors by giving priority to research and preventive programs looking in new directions.